Virtual Reality In Paraplegia: A Test Bed Applicationn - Riva, Giuseppe (International Journal of Virtual Reality, 2001)
The paper presents an overview of the ergonomic/design issues of a VR-enhanced orthopaedic appliance to be used in rehabilitation of patients with Spinal Cord Injury. First, some design considerations are described and an outline of aims which the tool should pursue are given. Finally, the design issues are described focusing both on the development of a test-bed rehabilitation device and on the description of a preliminary study detailing the use of the device with a long-term SCI patient. The basis for this approach is that physical therapy and motivation are crucial for maintaining flexibility and muscle strength and for reorganizing the nervous system after SCIs.